Scholarship Monitoring Information System at Ar-Raniry Islamic University - Ibrahim (International Journal Software Engineering and Computer Science (IJSECS), 2021)
The aim of this research is; 1) Able to design an information system for monitoring bidikmisi scholarships at Ar-Raniry State Islamic University Banda Aceh, and 2) Knowing the quality of the information system monitoring bidikmisi scholarships at Ar-Raniry State Islamic University Banda Aceh in providing information about bidikmisi scholarships based on ISO 9126 on functionality aspects, usability, efficiency, reliability, maintainability and portability. The design of an information system for processing scholarship monitoring data at the Ar-Raniry State Islamic University based on a website that the author designed consists of several stages, namely input design, output design, process design, control design, labor design, and cost design, while the application development uses a model prototyping. Based on the results of research and testing of the student monitoring information system at UIN Ar-Raniry Banda Aceh that has been carried out by the author, several conclusions can be drawn, namely; 1) This study succeeded in creating a student monitoring information system at UIN Ar-Raniry Banda Aceh, and 2) This research succeeded in collecting and reporting data on scholarships and orphaned students.